“Lo notas, lo sientes” Retóricas sobre prácticas de discriminación racial - ESCUDERO ZABALA, LAURA (2018)
Identifying and interpreting racial discrimination practices is a complex issue. This text presents an analysis based on ethnographic field work with racialized migrants in the context of the Spanish city of Madrid. Specifically, it is an approach to the rhetorical forms which people have to explain that they have experienced and suffered racist discrimination practices. In this sense, beyond the spectacular practices of discrimination such as aggression or discursive offenses, I will observer more closely those accounts which speak about more ambiguous practices, more hidden; to see how they subjectively construct that what they perceive as objective.